Herbal biomolecules in healthcare applications - Mandal, Subhash C.; Nayak, Amit Kumar, 1979-; Dhara, Amal Kumar (Academic Press, 2022)
Herbal Biomolecules in Healthcare Applications presents extensive detailed information on all the vital principles, basics and fundamental aspects of multiple herbal biomolecules in the healthcare industry. This book examines important herbal biomolecules including alkaloids, glycosides, flavonoids, anthraquinones, steroids, polysaccharides, tannins and polyphenolic compounds, terpenes, fats and waxes, proteins and peptides, and vitamins. These herbal biomacromolecules are responsible for different bioactivities as well as pharmacological potentials. A systematic understanding of the extraction, purification, characterization, applications of these herbal biomolecules and their derivatives in healthcare fields is developed in this comprehensive book. Chapters explore the key topics along with an emphasis on recent research and developments in healthcare fields by leading experts. They include updated literature review of the relevant key topics, good quality illustrations, chemical structures, flow charts, well-organized tables and case studies. Herbal Biomolecules in Healthcare Applications will be useful for researchers working on natural products and biomolecules with bioactivity and nutraceutical properties. Professionals specializing in scientific areas such as biochemistry, pharmacology, analytical chemistry, organic chemistry, clinics, or engineering focused on bioactive natural products will find this book useful.